2018
DOI: 10.4317/jced.54766
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic analysis of gingival lesions: A 20-year retrospective study at one academic dental center

Abstract: BackgroundThe gingiva is part of the periodontium supporting structures surrounding the teeth and commonly involved in gingival and periodontal conditions. Assessing the distribution of gingival lesions is important for evaluating the prevalence of periodontal disease in the population to optimize the oral health care services. The purpose of this study is to report the frequency and distribution of gingival lesions biopsied from 1996–2016.Material and MethodsThis cross-sectional retrospective study retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 12 publications
7
19
1
Order By: Relevance
“…Peripheral fibroma may show calcified bone-like structures in the form of osteoid or the calcification may resemble cementum-like substance. 27,32) In case-2 the connective tissue is covered with ulcerated and acanthotic stratified squamous epithelium and stroma is showing few calcifications in the form of osteoid (Figure 3b). The overgrowth was involving midline in relation to diastema of #12 and #21.…”
Section: Discussionmentioning
confidence: 98%
“…Peripheral fibroma may show calcified bone-like structures in the form of osteoid or the calcification may resemble cementum-like substance. 27,32) In case-2 the connective tissue is covered with ulcerated and acanthotic stratified squamous epithelium and stroma is showing few calcifications in the form of osteoid (Figure 3b). The overgrowth was involving midline in relation to diastema of #12 and #21.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is in accordance with almost every previous study on this subject. The most common lesion type in several studies was PG ( Ababneh, 2006 , Shamim et al, 2008 , Effiom et al, 2011 , Alblowi and Binmadi, 2018 ), while other reports found fibromas to be the most common of the four dominant lesions ( Zhang et al, 2007 , Buchner et al, 2010 , Hernandez-Rios et al, 2018 , Li et al, 2021 ). There may be a true difference in the prevalence of these four lesions based on specific geographical locations, or it may be related to the timing of presentation, as it has been suggested that long-standing PGs can mature into fibromas, which would explain the predominance of fibromas in some studies ( Eversole and Rovin 1972 ).…”
Section: Discussionmentioning
confidence: 98%
“…One of the problems associated with the true prevalence of benign tumors in the gingiva is that the classification was not consistent across the various studies. Some studies categorized reactive entities, such as POFs, giant cell fibromas, fibromas, angiofibromas, and squamous papillomas, as benign tumors ( Stablein and Silverglade, 1985 , Ababneh, 2006 , Shamim et al, 2008 , Alblowi and Binmadi, 2018 , Hernandez-Rios et al, 2018 ), which may account for the relatively high prevalence reported in those studies. In the present study, any lesion in which the major pathology was a non-neoplastic hyperplasia of fibrous and/or epithelial tissue was classified as reactive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As such, the oral cavity can be broadly divided into the lips, oral tongue, floor of the mouth, buccal mucosa, gingiva, retromolar trigone, and hard palate. 1 The gingiva is the third most common site of oral SCC, after the tongue and floor of the mouth 2,3 ; however, because gingival malignancies are infrequent relative to other benign gingival lesions, 4,5 gingival cancer poses a diagnostic challenge for clinicians, who may not suspect a malignancy in light of other more commonly encountered pathologies. Furthermore, because the attached gingiva is relatively thin, gingival cancers show early invasion of the underlying bone, and the prognostic implications of this behavior are presently unclear.…”
mentioning
confidence: 99%